PENGARUH PENAMBAHAN FLY ASH (CANGKANG TELUR DAN SEKAM PADI) DENGAN KUAT TEKAN BETON NON STRUKTURAL - Al Fauzi, Dwiki Wahyu; Affandy, Nur Azizah; Agustapraja, Hammam Rofiqi; Lubis, Zulkifli (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Using alternative materials in construction, such as eggshell fly ash (CT) and rice husk (SP), is increasingly important in reducing environmental impact. This research explores the influence of the proportion of CT and SP mixtures on concrete compressive strength and cracking. Both agricultural waste materials can potentially affect concrete characteristics, including binding ability, strength, and crack resistance. Testing was conducted using ASTM C standards for material and Indonesian national standards for concrete compressive strength and cracking. Variations in composition, 0% (A), 3% CT-5% SP (B), 5% CT-10% SP (C), and 7% CT-15% SP (D) by weight of cement, were performed on a total of 24 specimens. The results show that Concrete C had the highest compressive strength (212.2 kg/cm²), while Concrete D had the lowest compressive strength (165.56 kg/cm²). At 7 days, the highest cracking occurred in Concrete D (28.7 cm), and the lowest in Concrete C (22.3 cm). At 28 days, Concrete A had the highest cracking (26 cm), while Concrete C had the lowest (18.3 cm). This study provides valuable insights for the construction industry to utilize eggshell fly ash and rice husk in improving concrete performance and promoting sustainable development.